Imagos of Camelobaetidius cayumba (Traver & Edmunds, 1968) (Ephemeroptera: Baetidae) - Lima, Lucas R. C.; Boldrini, Rafael; Pinheiro, Ulisses (Zootaxa, 2012)
The genus Camelobaetidius Demoulin (Ephemeroptera: Baetidae) is represented in South America by 28 species: 19 of them are described based on nymphs, three based solely on adults, and only six based on nymphs and adults (Salles & Serrão, 2005; Dominguez et al., 2006; Boldrini & Salles, 2009; Salles & Nascimento, 2009; Boldrini et al., 2010). Camelobaetidius cayumba (Traver & Edmunds, 1968) was described from nymphs and can be distinguished, among other characteristics, by the inner margin of the second segment of labial palp pointed, thoracic gill absent at base of forelegs, claws with 15–18 denticles, and terminal filament about as long as cerci. It has been reported from Peru (Traver & Edmunds, 1968), French Guiana (Thomas et al., 2003), and Brazil (Salles & Serrão, 2005). The aim of the present paper is to describe the adults of C. cayumba from reared nymphs. The specimens were collected on rocky substrate of streams, and the adults were obtained by rearing these nymphs in the laboratory. Terms used in descriptions of thorax are in accordance to Kluge (1994). The material examined is housed in the Zoological Collection Norte Capixaba, Universidade Federal do Espírito Santo, São Mateus, ES (CZNC), Instituto Nacional de Pesquisas da Amazônia, Manaus, AM (INPA), and Entomological Collection of the Universidade Federal de Pernambuco, Recife, PE (UFPE).